1986
DOI: 10.1346/ccmn.1986.0340605
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Variation in Component Layers in Natural Illite/Smectite

Abstract: Abstract--Published chemical data for suites of mixed-layer minerals from diagenetic sedimentary rocks, hydrothermally altered tufts, and a metasomatic bentonite bed indicate that the layer charge and composition of the different components of illite/smectite (I/S) differ from one geological environment to another. It appears that the composition of the elemental smectite and illite layers in the I/S is more or less constant for samples within each geologic setting. In the examples considered, the smectite lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…The present study was undertaken in an attempt to verify these diverse findings, as well as equally diverse opinions on the charge density of smectite layers (Nadeau & Bain, 1986;Srodori et al, 1986;Velde & Brusewitz, 1986). High-resolution transmission electron microscopy (HRTEM) was used to check the accuracy of TEM data.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…The present study was undertaken in an attempt to verify these diverse findings, as well as equally diverse opinions on the charge density of smectite layers (Nadeau & Bain, 1986;Srodori et al, 1986;Velde & Brusewitz, 1986). High-resolution transmission electron microscopy (HRTEM) was used to check the accuracy of TEM data.…”
mentioning
confidence: 82%
“…8 for all the sample sets discussed plus the Montana Cretaceous bentonites of Eslinger et al (1979) and the Kinnekulle Ordovician bentonites of Brusewitz (1986). The exchangeable cation analyses of the last two sets were questioned, but any possible error cannot affect the silicate layer composition appreciably.…”
Section: Silicate Layer Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Hansen and Lindgreen (1989) concluded that this sampie is a bentonite originating from volcanic ash, whereas the other samples originate from detrital, R0-ordered I/S with P~ ~0.65. According to Velde and Brusewitz (1986), I/S originating from volcanic ash has a larger tetrahedral charge than I/S in shales. Thus, the chemical results of the present investigation suggest that the I/S in sample 2/7-3,3365m formed from volcanic ash.…”
Section: Lattice Transformation During Illite Layer Formationmentioning
confidence: 99%
“…The R = 1 ordered structure was encountered for samples having 40 to 50% smectite layers. Estimation of percent smectite was made using the method of Velde et al (1986) for air-dried samples. These identification methods were used because of the low intensity of the smectite peaks at ~9A (indicating that a small number of layers is present in the crystallites) and because of the frequent interference of zeolite, mica, and quartz peaks with I/S reflections.…”
Section: Clay Mineralogymentioning
confidence: 99%